Dicer is selectively important for the earliest stages of erythroid development. - Buza-Vidas, N; Cismasiu, V; Moore, S; Mead, A; Woll, P; Lutteropp, M; Melchiori, L; Luc, S; Bouriez-Jones, T; Atkinson, D; O'Carroll, D; Jacobsen, SE; et al. (2012)
MicroRNAs (miRs) are involved in many aspects of normal and malignant hematopoiesis, including hematopoietic stem cell (HSC) self-renewal, proliferation, and terminal differentiation. However, a role for miRs in the generation of the earliest stages of lineage committed progenitors from HSCs has not been identified. Using Dicer inactivation, we show that the miR complex is not only essential for HSC maintenance but is specifically required for their erythroid programming and subsequent generation of committed erythroid progenitors. In bipotent pre-MegEs, loss of Dicer up-regulated transcription factors preferentially expressed in megakaryocyte progenitors (Gata2 and Zfpm1) and decreased expression of the erythroid-specific Klf1 transcription factor. These results show a specific requirement for Dicer in acquisition of erythroid lineage programming and potential in HSCs and their subsequent erythroid lineage differentiation, and in particular indicate a role for the miR complex in achieving proper balance of lineage-specific transcriptional regulators necessary for HSC multilineage potential to be maintained.